Quality of Life Theory I. The IQOL Theory: An Integrative Theory of the Global Quality of Life Concept - Soren Ventegodt; Joav Merrick; Niels Jorgen Andersen (The Scientific World Journal)
Quality of life (QOL) means a good life and we believe that a good life is the same as living a life with a high quality. This paper presents the theoretical and philosophical framework of the Danish Quality of Life Survey, and of the SEQOL, QOL5, and QOL1 questionnaires.The notion of a good life can be observed from subjective to the objective, where this spectrum incorporates a number of existing quality of life theories. We call this spectrum the integrative quality-of-life (IQOL) theory and discuss the following aspects in this paper: well being, satisfaction with life, happiness, meaning in life, the biological information system (balance), realizing life potential, fulfillment of needs, and objective factors.The philosophy of life outlined in this paper tries to measure the global quality of life with questions derived from the integrative theory of the quality of life. The IQOL theory is an overall theory or meta-theory encompassing eight more factual theories in a subjective-existential-objective spectrum. Other philosophies of life can stress other aspects of life, but by this notion of introducing such an existential depth into the health and social sciences, we believe to have taken a necessary step towards a new humility and respect for the richness and complexity of life.